Bringing multiple values to the table: assessing future land-use and climate change in North Kona, Hawaiʻi - Bremer, Leah L.; Mandle, Lisa; Trauernicht, Clay; Pascua, Puaʻala; McMillen, Heather L.; Burnett, Kimberly; Wada, Christopher A.; Kurashima, Natalie; Quazi, Shimona A.; Giambelluca, Thomas; Chock, Pia; Ticktin, Tamara (Ecology and society, 2018)
As ecosystem service assessments increasingly contribute to decisions about managing Earth’s lands and waters, there is a growing need to understand the diverse ways that people use and value landscapes. However, these assessments rarely incorporate the value of landscapes to communities with strong cultural and generational ties to place, precluding inclusion of these values- alongside others-into planning processes. We developed a process to evaluate trade-offs and synergies in ecosystem services across land-use scenarios and under climate change in North Kona, Hawaiʻi, a tropical dry ecosystem where water, fire, biodiversity, and cultural values are all critical considerations for land management decisions. Specifically, we combined participatory deliberative methods, ecosystem service models, vegetation surveys, and document analysis to evaluate how cultural services, regulating services (groundwater recharge, landscape flammability reduction), biodiversity, and revenue: (1) vary across four land-use scenarios (pasture, coffee, agroforestry, and native forest restoration) and (2) are expected to vary with climate change (representative concentration pathway (RCP) 8.5 mid-century scenario). The native forest restoration scenario provided high cultural, biodiversity, and ecosystem service value, whereas coffee's strongest benefit was monetary return. The agroforestry scenario offered the greatest potential in terms of maximizing multiple services. Pasture had relatively low ecological and economic value but, as with native forest and agroforestry, held high value in terms of local knowledge and cultural connection to place. Climate change amplified existing vulnerabilities for groundwater recharge and landscape flammability, but resulted in few shifts in the ranking of land-use scenarios. Our results demonstrate that cultural services need not be sacrificed at the expense of other management objectives if they are deliberately included in land-use planning from the start. Meaningfully representing what matters most to diverse groups of people, now and under a changing climate, requires greater integration of participatory methods into ecosystem service analyses.